REVIEW ARTICLE: AKTIVITAS FARMAKOLOGI TANAMAN PARIJOTO (Medinilla speciosa) - Luthfiana Nurulin Nafi’ah (Pusat riset dan Inovasi Nasional, 2022)
Indonesia has a variety of plants that have potential as medicinal ingredients. One of the plants that can be used as medicine for various diseases is the parijoto plant. Parijoto is a plant that belongs to the Melastomataceae family. Parijoto plants contain flavonoid compounds, saponins, tannins and terpenoids. The content of compounds contained in the parijoto plant has various pharmacological activities. This study aims to determine the pharmacological activity of the parijoto plant (Medinilla speciosa). The method used in this study is to use the literacy review method. Reference search is done by searching Google search, Google Scholar, PubMed according to the topic. Based on a review of several literatures, it is shown that the parijoto plant (Medinilla speciosa) has pharmacological activity as antibacterial, antibiofilm, antidiabetic, antifungal, antioxidant, anticholesterol, and cytotoxic.